Serum lipid reference values recommended during a twin pregnancy and evaluating its association with perinatal outcomes - Jiaqi Huang; Xinlu Meng; Jiaxin LI; Xiaoli Gong; Tianchen Wu; Huifeng Shi; Xiaona Li; Xueju Wang; Jing Yang; Yangyu Zhao; Yuan Wei (BMC, 2024)
Abstract Background Maternal lipid metabolism fluctuations have been shown to increase the risk of adverse pregnancy outcomes. However, there is no consensus over what constitutes normal maternal lipid values during twin pregnancy. Therefore, the aim of this study was to establish a serum lipid reference range for a twin pregnancy. Methods A retrospective survey was conducted, from 2011 to 2021, at the Peking University Third Hospital. A total of 881 twin pregnancies, with lipid data from early and middle pregnancies, were included. After excluding those with adverse pregnancy outcomes, we performed a descriptive analysis of total cholesterol (TC), triglycerides (TG), high-density lipid cholesterol (HDL-C), and low-density lipid cholesterol (LDL-C) levels, using the mean and standard deviation to determine appropriate percentiles. We later determined the lipid reference range in early and middle pregnancy based on the initial results. We evaluated Inappropriate lipid levels associations with pregnancy outcomes, including gestational diabetes, pregnancy-induced hypertension, small for gestational age. Results (1) Serum levels of TC, TG, LDL-C, and HDL-C increased significantly from early to late pregnancy, where the greatest increase was observed in TG. (2) Based on the results, we recommend that TC, TG, and LDL-C serum reference values during early and middle pregnancy should be less than the 95th percentile. On the other hand, HDL-C should be greater than the 5th percentile. During early pregnancy, the values recommended are TC < 5.31 mmol/L, TG < 2.25 mmol/L, HDL > 1.02 mmol/L and LDL < 3.27 mmol/L, and those during middle pregnancy are TC < 8.74 mmol/L, TG < 4.89 mmol/L, HDL > 1.25 mmol/L and LDL < 5.49 mmol/L, while the values during late pregnancy are TC < 9.11 mmol/L, TG < 6.70 mmol/L, HDL > 1.10 mmol/L and LDL < 5.81 mmol/L. Higher levels of blood lipids were associated with GDM, PE, SGA. Conclusions We suggested a reference ranges for blood lipids during the twin pregnancy in a Chinese population. The reference ranges recommended by this study can be used to identify women with twin pregnancies using unfavorable lipid values. Higher levels of blood lipids were associated with adverse pregnancy outcomes.